Education On The Quality of Work Life as a Basis Preparing a Strategy for Handling Turnover Intention - Santoso, Windu; Sudarsih, Sri (Jurnal Pengabdian Pada Masyarakat METHABDI, 2024)
Quality of work life (QWL) is needed to maintain the workforce so that there is no desire to change work places. In health services, the transfer of nurses to another workplace (turnover) can have a negative impact on providing patient care. The purpose of this service activity is to provide education about the quality of work life as a basis for developing strategies for handling turnover intention. The problem found is that educational activities about the quality of work life are very important to help nursing managers to retain nurses in the workplace. Many nurses are still not satisfied with their QWL so this will have an impact on turnover intentions and increased nurse turnover in several hospitals. This service activity is carried out in two stages, namely the preparation stage and the implementation stage. This education was provided to service participants consisting of nursing managers in several hospitals in the East Java region, totaling 13 nurses. Activities are carried out online via the zoom meeting room. The agreed strategy for handling treatment complications is: providing a minimum reward in accordance with the employee's minimum wage, in employee recruitment it is necessary to consider male nurses as a priority, considering the domicile and marital status as well as the prospective husband's/husband's place of work. The agreed strategy can be implemented in hospitals as an effort to reduce intensity turnover.